Oligonucleotide dendrimers: synthesis and use as polylabelled DNA probes. - Shchepinov, M S (1997)
Oligonucleotide dendrimers were synthesized using a novel phosphoramidite synthon, tris-2,2,2-[3-(4,4'-dimethoxytrityloxy) propyloxymethyl]ethyl- N , N -diisopropylaminocyanethoxy phosphoramidite. Label, incorporated using [gamma-32P]ATP and polynucleotide kinase, was increased in proportion to the number of 5'-ends. There was a similar increase in signal when these multiply labelled oligonucleotides were used as probes to oligonucleotide arrays. A dendrimeric oligonucleotide was used successfully as a primer in the PCR. The strand bearing the dendrimer was resistant to degradation by T7 Gene 6 exonuclease making it easy to convert the double-stranded product of the PCR to a multiply-labelled, single-stranded probe.